WHO OWNS NAHDLIYYIN? A Discourse Analysis of Islamic Identity in Social Media during the 2024 Indonesia Presidential Elections - Marijan, Kacung; Rachman, Rio Febriannur; Wibisono, Rizky Bangun; Suwarko, Andi (State Islamic University (UIN) of Sunan Ampel Surabaya, 2025)
The 2024 Indonesian presidential election witnessed the strategic appropriation of Islamic symbols and Nahdliyyin or the follower of Nahdlatul Ulama identity in political discourse, particularly on social media. While Nahdlatul Ulama has historically shaped Indonesian politics, existing studies overlook how Nahdliyyin identity is constructed and contested in digital spaces. This study fills that gap by analyzing social media narratives through Stuart Hall’s theory of representation and Michel Foucault’s concepts of discourse and power. Using qualitative discourse analysis, this research explores how Islamic identity is mobilized, negotiated, and challenged in online political debates. Findings suggest that Nahdliyyin identity is increasingly treated as a political object rather than a substantive ideological force, with digital narratives reducing it to mere symbolism for electoral gain. Social media amplifies elite-driven representations, sidelining grassroots interpretations and internal diversity. These findings highlight the commodification of Nahdliyyin identity in political campaigns, reinforcing the dominance of symbolic politics over substantive engagement with Islamic thought.